Finite element study : Effect of emergency brake on total knee arthroplasty - S. F., Iskandar; Mas Ayu, Hassan; Rosdi, Daud; Siti Haryani, Tomadi; A., Shah (Institution of Engineering and Technology, 2022)
Patients often ask whether they may resume driving after total knee arthroplasty (TKA). Driving a vehicle is necessary for mobility, flexibility, and independence, but it is often hampered by discomfort, the use of walking aids, and partial weight bearing after lower limb surgery. As a result, patients usually enquire about recovery durations and when they will be able to safely drive again after total knee arthroplasty (TKA). The aim of this project is to highlight the relevance of using FEM along with TKA in performing emergency brake. In this study, we used two different design (commercially available in the market as a reference and newly proposes design) which were constructed using Solidworks software. The load (effect inertia of emergency brake) are applied to the tibial component and femoral component were created with fixed boundary condition. The femoral component were adjusted to 00, while the tibial component were adjusted to 1200 to mimic the actual driving position. The currently available model and newly proposed model of TKA were used to compare the von mises stress distribution when it comes to the impact force during emergency braking situation. The maximum value of von mises stress for design 1 when comparing the 9.881x109 N/m^2was considerably significantly different with the value of 1.807x108 N/m^2 for design 2. It implies that the potential effect of the sorbothane in the design 2 which prominent as the impact absorber of the emergency brake. It can be concluded that the total knee arthroplasty (TKA) performed better with the sorbothane during emergency brake since the lower maximum stress in the TKA can reduce the possibility of failure of the polyethylene and thus can also reduce the possibility of failure of the tibia tray and loosening.